Verification of the model of predisposition in triathlon - structural model of confirmative factor analysis - Kovárová, L.; Kovár, K. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2013)
BACKGROUND: The triathlon is a combination of three different types of sport - swimming, cycling, and running. Each of these requires different top level predispositions and complex approach to talent selection is a rather difficult process. Attempts to identify assumptions in the triathlon have so far been specific and focused only on some groups of predispositions (physiology, motor tests, and psychology). The latest studies missed the structural approach and were based on determinants of sport performance, theory of sports training and expert assessment. OBJECTIVE: The aim of our study was to verify the model of predisposition in the short triathlon for talent assessment of young male athletes age 17-20 years. METHODS: The research sample consisted of 55 top level triathletes - men, who were included in the Government supported sports talent programme in the Czech Republic at the age of 17-20 years. We used a confirmative factor analysis (FA) and Path diagram to verify the model, which allow us to explain mutual relationships among observed variables. For statistical data processing we used a structure equating modeling (SEM) by software Lisrel L88. RESULTS: The study confirms best structural model for talent selection in triathlon at the age of 17-20 years old men, which composed seventeen indicators (tests) and explained 91% of all cross-correlations (Goodness of Fit Index /GFI/ 0.91, Root Mean Square Residual /RMSR/ 0.13). Tests for predispositions in triathlons were grouped into five items, three motor predispositions (swimming, cycling and running skills), aerobic and psychological predispositions. Aerobic predispositions showed the highest importance to the assumptions to the general factor (1.00; 0). Running predispositions were measured as a very significant factor (-0.85; 0.28) which confirms importance of this critical stage of the race. Lower factor weight showed clusters of swimming (-0.61; 0.63) and cycling (0.53; 0.72) predispositions. The psychological predispositions were found in the lowest effect (0.36; 0.87). CONCLUSIONS: We confirm predispositions and tests for measurement of its level for top level male triathletes in the junior category. The model is in practice today in the Czech Republic, where we used the test standards for dividing Government support of athletic talent.